The Berlin Aging Study 1998
DOI: 10.1017/cbo9780511586545.003
|View full text |Cite
|
Sign up to set email alerts
|

Sample Selectivity and Generalizability of the Results of the Berlin Aging Study

Abstract: In epidemiological investigations, one common but rarely analyzed threat to generalizability is sample selectivity or nonrandom sample attrition. In this chapter, we describe our approach to the study of selectivity and provide indepth analyses of the magnitude of sample selectivify in the Berlin Aging Study. Of all individuals eligible for participation (the verified parent sample, N = 1,908), 27Vo reached the highest level of participation (the Intensive Protocol, N = 516). \4/ith respect to levels of perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 37 publications
2
64
0
Order By: Relevance
“…This finding is in line with that of Lindenberger et al (1999), who analysed attrition in the BASE-I study, a probability sample of the elderly aged 74 and older in West Berlin. No health-related selectivity was found in the BASE-I study, except in regard to BMI.…”
Section: Attrition Over the Course Of Timesupporting
confidence: 90%
See 1 more Smart Citation
“…This finding is in line with that of Lindenberger et al (1999), who analysed attrition in the BASE-I study, a probability sample of the elderly aged 74 and older in West Berlin. No health-related selectivity was found in the BASE-I study, except in regard to BMI.…”
Section: Attrition Over the Course Of Timesupporting
confidence: 90%
“…But even surveys based on a probability sample face problems of selectivity due to selective unwillingness of randomly selected potential subjects (respondents) to participate in SOEP Survey Papers 229 the survey. Lindenberger et al (1999) and also Schaie et al (1973) emphasise that initial sample selectivity has to be distinguished from selectivity due to attrition.…”
Section: Sample Selectivitymentioning
confidence: 99%
“…The study design consists of a hierarchical sequence of four levels of participation, with increasing numbers of variables but decreasing numbers of participants at each consecutive level: the verified parent sample (n = 1,908); the short-contact sample (n = 1,264); the intake assessment sample (n = 928); and the intensive protocol sample (n = 516), used in the present study, with its 14 sessions of multidisciplinary assessment. Extensive selectivity analyses (Lindenberger et al, 1999) showed the intensive protocol sample to be a somewhat positive selection of the parent sample. The magnitude of the selectivity effects was largest for general intelligence, but it did not exceed half a standard deviation for any of the analyzed domains of functioning.…”
Section: Methods Participants and Samplingmentioning
confidence: 99%
“…Hierarchically nested selectivity analyses comparing the 516 individuals who were willing and able to complete the comprehensive t1 assessment with the total parent sample revealed that the 516 individuals were positively selected on a broad range of variables covering demographic, sensory/sensorimotor, life history, and intellectual domains (for details, see Lindenberger et al, 1999). However, with the exception of dementia prevalence, effect size estimates were well below 0.5 standard deviation.…”
Section: Participantsmentioning
confidence: 99%